ANALISIS PENGARUH KETERIKATAN MEREK, IDENTIFIKASI MEREK, DAN PERSEPSI NILAI TERHADAP MINAT MENGGUNAKAN KEMBALI BRANDED APPS PADA APLIKASI SHOPEE INDONESIA - Hanifa, Ima Utin; Kusumawardhani, Amie (Faculty of Economics and Business Diponegoro University, 2019)
The rapid technology development makes people to continue innovating in facilitating work. Companies are competing to improve their systems in marketing products to consumers to get maximum incomes by creating a practical systems for consumers to access information about their products, one of them is Shopee Indonesia through their products application or can be called branded apps. Shopee Indonesia app is designed to provide product information and easy access for consumers to buy the products, also facilitate communication between consumers and producers. Researcher aimed people who live in Java, have Shopee Indonesia application in their smartphone, and once purchased from the app to be this research’s sample. The number of samples used in this study are 101 respondents. The method of collecting data through questionnaire and the method of collecting samples is by non probability sampling technique. This study uses Multiple Linear Regression analysis technique estimated by SPSS 20.0. The results of this study indicate that brand attachment, brand identification, and perceived value have a positive and significant effect on continuance intention to use branded apps.